2008
DOI: 10.1002/ar.20753
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Mouse Genetic Background and Age on Anterior Lens Capsule Thickness

Abstract: Accurate lens capsule thickness measurements are necessary for studies investigating mechanical characteristics of the capsule. Confocal Z-axis imaging was used to measure the anterior lens capsule thickness of living intact lenses with minimal tissue manipulation. Measurements of the anterior capsule thickness is reported for the first time in young and old mice from four inbred strains, BALB/c, FVB/N, C57BL/6, and 129X1, and the outbred strain ICR. Our data demonstrates that the mouse anterior lens capsule c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 59 publications
3
27
0
Order By: Relevance
“…The primary goal of these experiments was to find out how the AFM measurements compare with elasticity measurements of lens capsule probed by conventional hydrostatic measurements (Fisher, 1969;Krag and Andreassen, 2003;Danysh et al, 2008). The Young's modulus of human lens capsule, as measured by AFM, was 3.92, 2.70 and 4.37 MPa for 3 lens capsules, similar to the data obtained by hydrostatic measurements (Fisher, 1969;Krag and Andreassen, 2003;Danysh et al, 2008).…”
Section: Age-dependent Changes In the Biophysical Properties Of The Amentioning
confidence: 86%
See 1 more Smart Citation
“…The primary goal of these experiments was to find out how the AFM measurements compare with elasticity measurements of lens capsule probed by conventional hydrostatic measurements (Fisher, 1969;Krag and Andreassen, 2003;Danysh et al, 2008). The Young's modulus of human lens capsule, as measured by AFM, was 3.92, 2.70 and 4.37 MPa for 3 lens capsules, similar to the data obtained by hydrostatic measurements (Fisher, 1969;Krag and Andreassen, 2003;Danysh et al, 2008).…”
Section: Age-dependent Changes In the Biophysical Properties Of The Amentioning
confidence: 86%
“…The primary goal of these experiments was to find out how the AFM measurements compare with elasticity measurements of lens capsule probed by conventional hydrostatic measurements (Fisher, 1969;Krag and Andreassen, 2003;Danysh et al, 2008). The Young's modulus of human lens capsule, as measured by AFM, was 3.92, 2.70 and 4.37 MPa for 3 lens capsules, similar to the data obtained by hydrostatic measurements (Fisher, 1969;Krag and Andreassen, 2003;Danysh et al, 2008). Further, the Young's modulus of the human lens capsule was in the same range as for the adult human ILM and for the embryonic chick ILM, despite the fact that the lens capsule is about 10-times thicker than the human and 100 times thicker that the embryonic chick ILM, emphasizing again that the Young's modulus is a measure for the biomechanical property of BMs and independent of the thickness of the sample.…”
Section: Age-dependent Changes In the Biophysical Properties Of The Amentioning
confidence: 99%
“…Indeed, proteins such as fibulin might play an ongoing role in shaping and maintaining tissues (Kubota et al, 2012). In addition, basement membranes show dramatic changes in structure with age (Candiello et al, 2010;Danysh et al, 2008;Khalil-Manesh and Price, 1985;Taylor and Price, 1982). It will be interesting to determine whether age-dependent alterations to basement membranes underlie any changes the structure and function of aged tissues.…”
Section: Discussionmentioning
confidence: 99%
“…However, thickness measurements of BMs have been traditionally based on transmission electron microscopy (TEM) imaging that requires chemical fixation and dehydration of the samples. Recently, the thickness of BMs was re-examined using atomic force microscopy (AFM) and confocal microscopy [20][23]; both techniques allow studying fully hydrated and unfixed BMs. The AFM studies on the chick ILM and human ILMs, as well as confocal microscopy studies on the lens capsule showed that the native and hydrated BMs are between two and four-times thicker than previously recorded.…”
Section: Introductionmentioning
confidence: 99%